Fatigue properties of wood at different load ratios tested at 50 Hz and 20 kHz. Issue 3 (14th March 2022) - Schönbauer, B.M.; Killinger, M.; Karr, U.; Fitzka, M.; Müller, U.; Teischinger, A.; Mayer, H.
Abstract: Fatigue properties of sycamore maple (Acer pseudoplatanus) under cyclic tension, cyclic compression and tension‐compression loading at 50 Hz are investigated. Furthermore, for the first time, fatigue test results of wood generated with the ultrasonic fatigue testing technique at 20 kHz under tension‐compression loading are presented. Cyclic properties are in line with the static properties – with the tensile strength being more than two times the compressive strength. Mean lifetimes of 10 6 cycles are found if the maximum tensile stress for cyclic tension is 69 %±8 % of the tensile strength and if the maximum compressive stresses for cyclic compression and tension‐compression are 75 %±7 % and 54 %±4 % of the compressive strength, respectively. Tension‐compression loading at 20 kHz delivers lifetimes comparable to servo‐hydraulic tests at 50 Hz, and no pronounced frequency effect on fatigue lifetime is found. Ultrasonic fatigue testing is therefore, in principle, appropriate for accelerated fatigue testing of wood up to the very high cycle fatigue regime. Tests up to 10 9 cycles show no evidence of a fatigue limit for sycamore maple. Abstract : Fatigue properties of sycamore maple at different load ratios are investigated, and a Haigh diagram is plotted. In addition to servo‐hydraulic testing at 50 Hz, the ultrasonic fatigue testing technique – operating at 20 kHz under tension‐compression loading – is for the first time employed to investigate the fatigue properties of wood. No pronounced frequency effect and no fatigue limit are found. Translation abstract: Die Ermüdungseigenschaften von Bergahorn (Acer pseudoplatanus) wurden unter Zugschwell‐, Druckschwell‐ und Wechselbeanspruchung bei 50 Hz untersucht. Zudem wurden erstmalig Versuche mit dem Ultraschall‐Ermüdungsprüfverfahren bei 20 kHz unter Wechselbeanspruchung an Holz durchgeführt. Die zyklischen Festigkeiten zeigen ein ähnliches Verhalten wie die statischen Festigkeiten – die Zugfestigkeit beträgt mehr als das Doppelte der Druckfestigkeit. Mittlere Lebensdauern von 10 6 Lastzyklen ergaben sich, wenn die maximale Zugspannung unter Zugschwellbeanspruchung 69 %±8 % der Zugfestigkeit und wenn die maximale Druckspannung unter Druckschwell‐ bzw. unter Wechselbeanspruchung 75 %±7 % bzw. 54 %±4 % der Druckfestigkeit beträgt. Die bei 50 Hz und 20 kHz ermittelten Lebensdauern stimmen gut überein und es zeigt sich kein wesentlicher Einfluss der Belastungsfrequenz auf die Ermüdungslebensdauer von Holz. Ultraschall‐Ermüdungsversuche sind daher geeignet, auch für Holz innerhalb kurzer Zeit aussagekräftige Ergebnisse im Bereich sehr hoher Lastspielzahlen zu generieren. Bis zu 10 9 Lastzyklen konnte für Bergahorn keine Dauerfestigkeit gefunden werden.